Real-world particle emissions and secondary aerosol formation from a diesel oxidation catalyst and scrubber equipped ship operating with two fuels in a SECA area. (1st January 2022) - Karjalainen, Panu; Teinilä, Kimmo; Kuittinen, Niina; Aakko-Saksa, Päivi; Bloss, Matthew; Vesala, Hannu; Pettinen, Rasmus; Saarikoski, Sanna; Jalkanen, Jukka-Pekka; Timonen, Hilkka
Abstract: SOx Emissions Control Areas (SECAs) have been established to reduce harmful effects of atmospheric sulfur. Typical technological changes for ships to conform with these regulations have included the combustion of low-sulfur fuels or installment of SOx scrubbers. This paper presents experimental findings from high-end real-time measurements of gaseous and particulate pollutants onboard a Roll-on/Roll-off Passenger ship sailing inside a SECA equipped with a diesel oxidation catalyst (DOC) and a scrubber as the exhaust aftertreatment. The ship operates between two ports and switched off the SOx scrubbing when approaching one of the ports and used low-sulfur fuel instead. Measurement results showed that the scrubber effectively reduced SO2 concentrations with over 99% rate. In terms of fuel, the engine-out PM was higher for heavy fuel oil than for marine gas oil. During open sea cruising (65% load) the major chemical components in PM having emission factor of 1.7 g kgfuel −1 were sulfate (66%) and organics (30%) whereas the contribution of black carbon (BC) in PM was low (∼4%). Decreased engine load on the other hand increased exhaust concentrations of BC by a factor exceeding four. As a novel finding, the secondary aerosol formation potential of the emitted exhaust measured with an oxidation flow reactor and an aerosol mass spectrometer was found negligible. Thus, it seems that either DOC, scrubber, or their combination is efficient in eliminating SOA precursors. Overall, results indicate that in addition to targeting sulfur and NOx emissions from shipping, future work should focus on mitigating harmful particle emissions. Graphical abstract: Image 1 Highlights: Real-world emissions of a ship equipped with a scrubber were studied on-board. Scrubber reduced SO2 concentrations with over 99% efficiency. PM during cruising was mainly sulfates (66%) and organics (30%), minorly BC (4%). MGO fuel decreased sulfates and organics but increased BC compared to HFO fuel. Secondary aerosol formation potential in the emitted exhaust was found negligible.